Concept of judicial protection of the housing rights of individuals - Холод, Руслан Віталійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article explores the concept of judicial protection of the housing rights in the context of substantive and procedural law that determine the content of the housing rights and interests of individuals. The author analyzes theoretical and legal approaches to the definition of the right to the protection of housing rights of individuals and its legal content. On the basis of understanding the essence of the legal norms the author determines the structure of the right to protection as a part of the objective and subjective rights. Concept of protection in the housing sector is considered as legal measures undertaken by individual self- recognition of the violation and restoration of these rights and legitimate interests of both users and owners. It is stated that in the judicial forms of protection, in turn, allocate general and special order violated rights .The right to housing is protected by Article 47 of the Constitution of Ukraine, and only in urgent cases related to saving lives and property, or to the direct pursuit of persons suspected of committing a crime, another possible established by law for entry into a dwelling or other property of a person for the examination and search.. Under the article 29 of Civil Code of Ukraine each individual personally or together with other persons have the right to protect their housing rights, which is implemented regulations that protect property rights.